2014
DOI: 10.1007/s00125-014-3463-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma isoflavone concentration is associated with decreased risk of type 2 diabetes in Korean women but not men: results from the Korean Genome and Epidemiology Study

Abstract: Aims/hypothesis To examine the association between soybean products and risk of type 2 diabetes, we measured four isoflavone biological markers-genistein, daidzein, glycitein and equol-in a nested case-control study. Methods The study population was composed of 693 cases (316 women and 377 men) and 698 matched controls (317 women and 381 men) within the Korean Genome and Epidemiology Study. The concentrations of isoflavone biomarkers were measured using HPLC-MS/MS on plasma samples that were collected at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 44 publications
1
33
1
Order By: Relevance
“…The plasma concentration of isoflavone in Asian populations is approximately 40 times more than the concentration in European populations. 46,48 It has been hypothesized that the clinical efficacy of isoflavone might be dependent on equol, which is transformed by the gut microbiome during digestion. Whereas the equol-producing rate of Western populations is 30-40%, that of Asian populations is as high as 80%.…”
Section: Colorectal Cancer In the Asia-pacific Regionmentioning
confidence: 99%
“…The plasma concentration of isoflavone in Asian populations is approximately 40 times more than the concentration in European populations. 46,48 It has been hypothesized that the clinical efficacy of isoflavone might be dependent on equol, which is transformed by the gut microbiome during digestion. Whereas the equol-producing rate of Western populations is 30-40%, that of Asian populations is as high as 80%.…”
Section: Colorectal Cancer In the Asia-pacific Regionmentioning
confidence: 99%
“…Among them, genistein and other phytoestrogens attract great interest, as they exhibit a plethora of biological actions, including breast and prostate cancer chemopreventive activity [17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids has been increasingly used in skin care and cosmetic products as an ultraviolet radiation protectant (Jimtaisong 2015; Peng et al 2015;Saewan & Jimtaisong 2015). Ko et al (2015) had found plasma that contain geneistein (isoflavone) correlated to decrease risk of type 2 diabetes in women. There is an association of the anti-diabetic effect of isoflavone towards their physiological changes.…”
Section: Pharmaceutical and Pharmacological Properties Of Flavonoidsmentioning
confidence: 99%